VELHO, Gilberto; DUARTE, Luiz Fernando (Orgs.). Gerações, família, sexualidade - Oltramari, Leandro Castro (Revista Estudos Feministas, 2010)
VELHO, Gilberto; DUARTE, Luiz Fernando (Orgs.). Gerações, família, sexualidade